2011
DOI: 10.1161/strokeaha.110.599068
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Induced by Electrical Stimulation Improves Motor Recovery in Postacute Hemiparetic Patients

Abstract: Background and Purpose-This study assessed whether cycling induced by functional electrical stimulation (FES) was more effective than passive cycling with placebo stimulation in promoting motor recovery and walking ability in postacute hemiparetic patients. Methods-In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
91
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 26 publications
1
91
0
4
Order By: Relevance
“…631 Similarly, a meta-analysis revealed the effectiveness of NMES at improving gait speed in subjects after stroke. 632 Several RCTs have observed improved recovery of gait function after stroke in the chronic 550,[633][634][635] and acute phases 636,637 when NMES was applied in conjunction with a conventional rehabilitation program. Studies comparing the use of an AFO to NMES in controlling foot drop during walking have found similar results.…”
mentioning
confidence: 99%
“…631 Similarly, a meta-analysis revealed the effectiveness of NMES at improving gait speed in subjects after stroke. 632 Several RCTs have observed improved recovery of gait function after stroke in the chronic 550,[633][634][635] and acute phases 636,637 when NMES was applied in conjunction with a conventional rehabilitation program. Studies comparing the use of an AFO to NMES in controlling foot drop during walking have found similar results.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19] Using surface electrical stimulation to muscles of the lower extremities, the FES cycle can provide for passive, active with volitional control, or FES-assisted cycling. The newest FES devices allow the individual to remain seated in a supported position in front of the cycle ergometer, minimizing the need for wheelchair transfers.…”
mentioning
confidence: 99%
“…For the rehabilitation purpose, many studies have used stationary FES cycling system such Copyright c 2016 The Institute of Electronics, Information and Communication Engineers as bicycle ergometer combined with FES [13]- [20]. From these studies, FES cycling has been shown to be effective in fitness or rehabilitation training mainly for stroke patients [10], [14], [17]- [19], [21].…”
Section: Introductionmentioning
confidence: 99%